Learning to Be Employable Through Volunteering: A Qualitative Study on the Development of Employability Capital of Young People - Giancaspro, Maria Luisa; Manuti, Amelia (Frontiers in Psychology, 2021)
The research aimed to study voluntary work as a context of informal and non-formal learning and vocational guidance, useful to understand one’s own inclinations, to develop skills and abilities and to increase future employability. Participants were 38 young volunteers included in the Universal Civil Service, a national program addressed to young people, aged up to 28 years, who want to engage themselves in activities useful for the community and in the meantime who wish to measure themselves with an informal working context. Participants were invited to describe their volunteering experience in a diary page, highlighting if and to what extent this context contributed to enhance their employability capital, namely the asset of skills, knowledge and networks acquired, that they could transfer to a future professional domain. The narrative data collected were examined through diatextual analysis, a specific address of discourse analysis precious to catch the relationship between enunciators, text and context of the talk. This qualitative analysis allowed to investigate the meanings young people attributed to these activities and the strategies they adopted to capitalize the intangible asset of personal resources acquired through non-formal and informal pathways in order to increase their future employability.